2009
DOI: 10.1007/s11738-009-0289-0
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous polyamine profiles in different tissues of Coffea sp., and their levels during the ontogeny of fruits

Abstract: Polyamines are essential compounds for growth and development in plants. An attempt has been made to find out the endogenous polyamine profiles in various parts and during the ontogeny of fruit formation of two commercially important Coffea species viz., arabica and canephora. Putrescine (Put), spermine (Spm) and spermidine (Spd) are the predominant polyamines during the ontogeny of fruit and their level increased with the advancement of fruit development. However, in the initial stages of flower and fruit dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Coffee polyamines profiles have been measured (Sridevi, Giridhar, Ravishankar, 2009) observed that processing conditions of unripe coffee beans influence the resulting concentrations of 102 biogenic amines, particularly spermine, spermidine, histamine, and cadaverine (Dias et al, 2012 ). drying, resulting in reduced formation of biogenic amines.…”
Section: Introduction 41mentioning
confidence: 99%
“…Coffee polyamines profiles have been measured (Sridevi, Giridhar, Ravishankar, 2009) observed that processing conditions of unripe coffee beans influence the resulting concentrations of 102 biogenic amines, particularly spermine, spermidine, histamine, and cadaverine (Dias et al, 2012 ). drying, resulting in reduced formation of biogenic amines.…”
Section: Introduction 41mentioning
confidence: 99%
“…Interplay of polyamine and ethylene in organogenesis has been reported (Bais et al 2000). Polyamines occur in both free and conjugated forms, and its endogenous levels depend on the external conditions of light and temperature (Galston and KaurSawhrey 1990) and also vary in different tissues of plant (Sridevi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Because Trig alkaloids gives rise to many flavour (aroma) compounds, like alkyl-pyradines and pyrroles (De Maria, Trugo, Moreira & Werneck 1994). In view of this, the levels of Trig in developing seeds are important though we don't have any information about the actual role of this in developing fruits unlike polyamines and free diterpenes (Sridevi, Giridhar & Ravishankar, 2009, 2010. Shimizu and Mazafera (2000) showed the role of trigonelline during inhibition and germination of coffee seeds.…”
Section: Journal Of Food Studiesmentioning
confidence: 99%